Comparison of heart rate variability according to performance in elite female judo athletes - Bae, M.-J.; Kim, H.-C.; Park, K. J. (Journal of The Korean Society of Physical Medicine, 2020)
PURPOSE: This study was to investigate examined the differences in the autonomic nervous functions of elite femalejudo athletes according to their performance by measuring theheart rate variability (HRV). METHODS: Sixteen elite female judo players participatedin this study. The participants were divided into a high performance and low performance group according to theresults of their competitions. The HRV (mean heart rate,SDNN, RMSSD, TP, LF, HF, LF/HF ratio) was measured inthe resting status. A t-test was used to compare the two groups,and bivariate logistic regression analysis was performed todetermine the HRV elements that affect performance. Thedata were analyzed using IBM SPSS Statistics ver. 24.0 (IBMCo., Armonk, NY, USA). RESULTS: The mean heart rate was higher in the high performance group (72.88) than in the low performance group (64.75) (p=.049). The LF/HF ratio was higher in the highperformance group (3.43) than in the low performance group (0.83), and the results were significant (p=.038). No HRVelements having a significant effect on the performance wereobserved. CONCLUSION: This study showed that the activity of thesympathetic nervous system was dominant in the highperformance group in the resting status than in the lowperformance. The high performance group is believed to bein the overtraining status who experience more stress.